Sabry (on the right), Nasser's special adviser on foreign affairs, gives a press conference. On his right the Egyptian Ambassador Hassan El-Feki
Sabry (on the right), Nasser's special adviser on foreign affairs, gives a press conference. On his right the Egyptian Ambassador Hassan El-Feki.